Exploring a mobile phone user's attitude toward watching TV content on a mobile phone – uses and gratifications perspective. Issue 2 (29th April 2020) - Shin, Soo Il; Kim, J.B.; Han, Sumin; Lee, Sangmi
Abstract : Purpose: The purpose of this study is to examine factors affecting mobile phone users' attitude toward watching TV content on a mobile device. Under the uses and gratifications theory, the current study examined attitude toward watching TV content on a mobile phone, with antecedents of affinities for both watching TV content and a mobile phone use. Design/methodology/approach: The current study adopted a construct of relative advantage as a mediator between affinities and attitude, and four moderators that affect the relationship between relative advantage and attitude. The study then analyzed 430 survey responses from public mobile phone users with a generalized linear model. Findings: Research findings reveal that both affinities are significantly associated with the relative advantage of watching TV content on a mobile phone. Relative advantage plays a salient role in explaining attitudes toward watching TV content on a mobile phone. The relationship between attitude and relative advantage was significantly affected by relaxation, fashion status and accessibility. Originality/value: This study contributes to media literature, especially where new, applied technology is considered. Particularly, the current research theoretically explains rationale behind a mobile phone user's positive attitude toward watching TV content on a mobile phone, and potential implication of the current and increasing trend of broadcasting individual content through social media outlets.